Estudio del manejo de la información de el comercio y el universo sobre la xenofobia a ciudadanos colombianos a partir del caso angostura en el periodo abril – agosto de 2015 - García Zapata, Marcelo Andrés (2016)
Relations between Ecuador and Colombia were affected on March 1st 2008 by a bombing carried out at a camp of the Revolutionary Armed Forces of Colombian, Ecuadorian territory near northern border where the top leader of the FARC guerrillas including several killed Raul Reyes. From this fact the migration of people was evidenced most often by the authorities of both countries, most cases reflected the violence generated by the FARC, as a consequence the presence of Colombians in Ecuador sparked xenophobia in our country….